Effects of Galvanic Vestibular Stimulation on Vestibular Compensation in Unilaterally Labyrinthectomized Mice - Nam, Gi-Sung; Nguyen, Thanh Tin; Kang, Jin-Ju; Han, Gyu Cheol; Oh, Sun-Young (Frontiers in Neurology, 2021)
Objectives: To investigate the ameliorating effects of sinusoidal galvanic vestibular stimulation (GVS) on vestibular compensation from unilateral vestibular deafferentation (UVD) using a mouse model of unilateral labyrinthectomy (UL). Methods: Sixteen male C57BL/6 mice were allocated into 2 groups that comprise UL groups with GVS (GVS group, n=9) and without GVS intervention (non-GVS group, n=7). In the experimental groups, we assessed vestibulo-ocular reflex (VOR) recovery before (baseline) and 3, 7 and 14 days after surgical unilateral labyrinthectomy. In the GVS group, stimulation was applied for 30 minutes daily from the postoperative day (POD) 0 to 4 via electrodes inserted subcutaneously next to both bony labyrinths. Results: Locomotion and VOR were significantly impaired in the non-GVS group compared to baseline. The mean VOR gain of the non-GVS group was attenuated to 0.23 at POD 3 and recovered continuously to the value of 0.54 at POD 14, but did not reach the baseline values at any frequency. GVS intervention significantly accelerated recovery of locomotion, as assessed by the amount of circling and total path length in the open field tasks compared to the non-GVS groups on PODs 3 (p<0.001in both amount of circling and total path length) and 7 (p<0.01 in amount of circling and p<0.001 in total path length, Mann-Whitney U tests). GVS also significantly improved VOR gain compared to the non-GVS groups at POD 3 (p<0.001), 7 (p<0.001) and 14 (p<0.001, Independent t-tests) during sinusoidal rotations. In addition, the recovery of the phase responses and asymmetry of the VOR was significantly better in the GVS group than in the non-GVS group until 2 weeks after UVD (phase, p=0.001; symmetry, p<0.001 at POD 14). Conclusion: Recoveries for UVD-induced locomotion and VOR deficits were accelerated by an early intervention with GVS, which implies that GVS has the potential to improve vestibular compensation in patients with acute unilateral vestibular failure.